2013
DOI: 10.4038/sljch.v42i2.5628
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine abnormalities in children with Beta thalassaemia major

Abstract: Background: Endocrine complications in βthalassaemia major patients in developing countries are likely to occur at younger ages due to suboptimal iron chelation. Objective:To assess the prevalence of endocrine abnormalities and correlate serum ferritin, degree of anaemia and liver dysfunction with endocrine dysfunction Method: A cross sectional study was carried out in B. J. Wadia Hospital, over a period of 2 years, on all children with β-thalassemia major over the age of 4 years receiving regular blood transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(16 reference statements)
1
5
1
Order By: Relevance
“…A similar study investigating the prevalence of endocrine disorders in patients with transfusion-dependent thalassemia showed that the most common endocrinopathy encountered was a delayed puberty at a prevalence of 68%, followed by low bone mineral density in 56.1% and short stature in 52.5% of the total sample size. 10 The results are somewhat similar to the findings of our study, in which short stature was the most common complication but with a prevalence of 39.5%, though this was succeeded by the development of diabetes mellitus in 29.4% of all sample size. Furthermore, gender was considered as a risk factor for the development of short stature as males were found to be more predisposed than females ( p =0.001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar study investigating the prevalence of endocrine disorders in patients with transfusion-dependent thalassemia showed that the most common endocrinopathy encountered was a delayed puberty at a prevalence of 68%, followed by low bone mineral density in 56.1% and short stature in 52.5% of the total sample size. 10 The results are somewhat similar to the findings of our study, in which short stature was the most common complication but with a prevalence of 39.5%, though this was succeeded by the development of diabetes mellitus in 29.4% of all sample size. Furthermore, gender was considered as a risk factor for the development of short stature as males were found to be more predisposed than females ( p =0.001).…”
Section: Discussionsupporting
confidence: 90%
“…19 Hypoparathyroidism as a complication of transfusion-dependent hemoglobinopathies was reported by some studied in prevalences of 9.4 %and 13.2% whereas others reported a prevalence of 0%. 10,14,19 In published literature, it has a more frequent prevalence between 3.6% to 22.5%; however, in the present study it was considered the least frequent endocrinopathy with an overall prevalence of only 2.5%. 20,21 In addition, vitamin D deficiency was studied as an association in patients with severe hemoglobinopathies.…”
contrasting
confidence: 58%
“…In contrast, Joshi et al reported the range of serum ferritin level of 5,295 (SD 2,736) ng/mL and Hb value of 7.8 (SD 0.6) g/dL were not significantly different in the thalassemia group and normal group. 25 Another study found a correlation between serum ferritin level >2,000 ng/mL and height-for-age (Z-score) >10-15 years (P<0.001). 23 Study in Indonesia reported a correlation between serum ferritin level (OR=3.248; 95%CI 1.304 to 8.086) and growth disorder in thalassemia patients (OR=3.964; 95%CI 1.192 to 13.190).…”
Section: Resultsmentioning
confidence: 95%
“…Β-thalassemia is the most frequent type of thalassemia. Anemia and iron overload are responsible for endocrine dysfunction in β-thalassemia [2]. Though meticulous management has prolonged the life expectancy of these patients, they tend to suffer from growth retardation and endocrine dysfunction that are multifactorial in etiology and may be can't prevent by treatment [3].…”
Section: Introductionmentioning
confidence: 99%